GEOCHEMICAL DIFFERENTIATION OF THE LITHOGENIC BASE OF THE LANDSCAPES OF THE GREATER CAUCASUS - Tatyana Vasilyevna Degtyarova; Andrey Aleksandrovich Likhovid; Natalya Gennadievna Likhovid (Наука. Инновации. Технологии)
Introduction: the relevance of the study is due to the need to identify the role of the lithogenous basis of the landscapes of the Greater Caucasus in the formation of their geo-chemical features and patterns of migration and concentration of chemical elements in various landscape and geochemical conditions. The purpose of the article is to study the specific geochemical differentiation of near-surface (soil-forming) sediments of the landscapes of the Greater Caucasus. Materials and methods: a method was used to compare the chemical composition of the main soil-forming complexes of the physico-geographical subregions of the northern slopes of the Greater Caucasus with a regional lithogeochemical background. Results: Geochemical differentiation of soil-forming rock complexes was revealed for the physico-geographical subregions of the northern slopes of the Greater Caucasus, which are allocated in the physico-geographical zoning of the territory. Areas of distribution of individual complexes of soil-forming rocks are considered as litho-geochemical fields of regional geosystems. Based on the calculation of regional concentration coefficients for lithogeochemical fields, the above and below-back-ground associations of chemical elements were distinguished relative to the regional lithogeochemical background, for which the average content of chemical elements in the soil-forming complexes of the North Caucasus was adopted. Discussion and conclusion: the authors concluded that the formation of geochemical features of surface soil-forming complexes of sediments in the landscapes of the northern slopes of the Greater Caucasus was greatly influenced by long-term weathering processes during the orogenic stage of the region's development in the Late Cenozoic. The practical signiicance of the results obtained is to determine the basic information on the lithogenic basis of the landscapes of the Greater Caucasus, which is necessary for sound geoecological monitoring.